2015
DOI: 10.1177/0269216315616524
|View full text |Cite
|
Sign up to set email alerts
|

Euthanasia and physician-assisted suicide: A white paper from the European Association for Palliative Care

Abstract: The European Association for Palliative Care feels that it is important to contribute to informed public debates on these issues. Complete consensus seems to be unachievable due to incompatible normative frameworks that clash.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
151
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(167 citation statements)
references
References 41 publications
(71 reference statements)
3
151
0
13
Order By: Relevance
“…23 Official reports from Oregon, Vermont and Washington, where only physician-assisted suicide is legal and euthanasia is not, have also shown an increase in the number of officially reported deaths, although with much lower incidences than in Belgium and the Netherlands. [23][24][25][26][27][28] Even within Belgium, development of the practice has differed between Flanders and Wallonia, as our study shows. The relative underrepresentation of reported euthanasia cases from the French-speaking community and the differences in case characteristics corroborate previous studies that found significant differences between Flanders and Wallonia in terms of practice, attitudes and knowledge about euthanasia.…”
Section: Discussionmentioning
confidence: 90%
“…23 Official reports from Oregon, Vermont and Washington, where only physician-assisted suicide is legal and euthanasia is not, have also shown an increase in the number of officially reported deaths, although with much lower incidences than in Belgium and the Netherlands. [23][24][25][26][27][28] Even within Belgium, development of the practice has differed between Flanders and Wallonia, as our study shows. The relative underrepresentation of reported euthanasia cases from the French-speaking community and the differences in case characteristics corroborate previous studies that found significant differences between Flanders and Wallonia in terms of practice, attitudes and knowledge about euthanasia.…”
Section: Discussionmentioning
confidence: 90%
“…One International collaborative guide, on artificial nutrition and hydration guidelines for those attending to patients at the end of their lives, emphasizes that the dying process should not be prolonged [19]. On the other hand, one white paper from the European association for palliative care (EAPC) states that the provision of euthanasia and PAS should not be included into the practice of palliative care [15]. One paper from the USA is a national survey of physicians about receiving requests for assisted suicide or euthanasia, and their compliance with the requests [20].…”
Section: Exclusion/inclusion Criteriamentioning
confidence: 99%
“…Francis Bacon in 1605 first coined the term in reference to alleviating suffering of human patients [14]. It is defined by the European Association of Palliative Care as a physician (or other person) intentionally killing a person by the administration of drugs, at that person's voluntary and competent request [15] (p. 5).…”
Section: Introductionmentioning
confidence: 99%
“…Im letzten Jahr sah die Europäische Palliativgesellschaft (EAPC) die Notwendigkeit, zu Euthanasie und ärztlich assistiertem Suizid Stellung zu nehmen und zum Ausdruck zu bringen, dass "Euthanasie kein Teil der Palliativversorgung ist" [1]. In Deutschland hat der Deutsche Bundestag am 06.…”
Section: Introductionunclassified